Case report: Transcatheter tricuspid valve intervention using K-Clip™ system after prior Kay’s annuloplasty - Wu, Shengjun; Dai, Xiaoyi; Liu, Lingshan; Yuan, Shuai; Teng, Peng; Ni, Yiming (Frontiers in Cardiovascular Medicine, 2023)
The K-Clip TM system is emerging as an alternative to correct tricuspid regurgitation for patients with high surgical risk. However, patients with recurrent severe tricuspid regurgitation after prior Kay's annuloplasty are generally deemed to be not candidacy for K-Clip TM implantation. Herein, we report a 63-year-old woman with recurrent symptomatic torrential tricuspid regurgitation 5 years after double valve replacement with Kay's annuloplasty of the tricuspid valve. The K-Clip TM was successfully implanted and the severity of tricuspid regurgitation and dimensions of tricuspid annulus achieved significant reduction. In conclusion, K-Clip TM can be still feasible and effective for patients with prior Kay's annuloplasty, but the indications become more rigorous and the evaluation should be more comprehensive.